Case Report: A Rare Heterozygous ATP8B1 Mutation in a BRIC1 Patient: Haploinsufficiency? - Bing, Hao; Li, Yi-Ling; Li, Dan; Zhang, Chen; Chang, Bing (Frontiers in Medicine, 2022)
Benign recurrent intrahepatic cholestasis (BRIC) is an autosomal recessive disorder characterized by recurrent cholestasis. ATPase class I, type 8B, member 1 (ATP8B1) encodes familial intrahepatic cholestasis 1 (FIC1), which acts as a phosphatidylserine reversing enzyme in the tubule membrane of hepatocytes to mediate the inward translocation of phosphatidylserine (PS). At present, dozens of ATP8B1 pathogenic mutations have been identified that mainly cause BRIC1 and progressive familial intrahepatic cholestasis 1 (PFIC1). The diagnosis of BRIC1 is based on symptoms, laboratory tests, imaging, liver histology, and genetic testing. BRIC1 treatment seeks to prevent recurrence and reduce disease severity. At present, the main treatment methods include ursodeoxycholic acid (UDCA), rifampin, cholestyramine and haemofiltration, and endoscopic nasobiliary drainage (ENBD). Here, we report a 17-year-old patient with cholestasis who has a rare heterozygous ATP8B1 gene mutation (p.T888K). The patient was treated with UDCA, glucocorticoids and haemofiltration, after which bilirubin levels gradually returned to normal. This case was thought to be caused by an ATP8B1 heterozygous mutation, which may be related to haploinsufficiency (HI).